Auditing profession given the accounting reform in Algeria - قادري عبد القادر (Finance and Business Economies Review, 2020)
The purpose of this paper is to highlight the profession of the Auditing as one of the key professions for providing external auditing services in Algeria, in that, the study, in its theoretical aspect, has depended on highlighting audit services provided by the external auditor, while the practical side focused on regulating and practicing the auditing profession through the laws that regulate it in the framework of the accounting reform that Algeria has undertaken from 2004 to now.